2014
DOI: 10.5005/jp-journals-10024-1612
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and Practice of Pediatricians and Pharmacists in Riyadh City toward the use of Sugar free Medications

Abstract: There is a considerable knowledge about SFMs and its impact on dental caries, among pediatricians and pharmacists participated in this study. However, their attitude toward prescribing or dispensing SFMs was not positive and may be linked to the gap in knowledge. Further training and education of healthcare providers regarding the use of SFMs and its negative impact on dental caries has to be reiterated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 10 publications
1
15
0
Order By: Relevance
“…This finding was similar to other studies. [714] Most of the pediatricians were of the opinion that sugar-free medications are not as sweet as sugar-containing medicaments and more expensive. Similar results were also reported by Bawazir et al .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This finding was similar to other studies. [714] Most of the pediatricians were of the opinion that sugar-free medications are not as sweet as sugar-containing medicaments and more expensive. Similar results were also reported by Bawazir et al .…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were also reported by Bawazir et al . [7] The sugar-free medicaments are actually sweet which are sweetened with anticariogenic and anti-acidogenic sweetening agents such as xylitol, mannitol, and sorbitol. [15] Other misconception about sugar-free medications may be due to the term “sugar free” as pediatricians would have thought that it is synonym to “sweet-free;” therefore, the use of “sucrose-free” or “noncariogenic medications” could improve the attitude toward sugar-free medications.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, Pediatricians should be aware about the deleterious relationship between antibiotics and dental caries. Pierro VVS, Barcelous R (2001) 15 in Brazil, Bawazir OA et al, (2014) 16 in Riyadh, Folayan MO et al, (2012) 17 in Nigeria conducted studies on Pediatrician's perception about the use of antibiotics causing dental caries and reported that pediatricians did not perceive the correct relationship between the presence of fermentable carbohydrates in antibiotics and dental caries.…”
Section: Introductionmentioning
confidence: 99%